Determinants of change in timely first antenatal booking among pregnant women in Ethiopia: A decomposition analysis. - Melaku Yalew; Bezawit Adane; Yitayish Damtie; Bereket Kefale; Reta Dewau; Kefale Mektu; Mastewal Arefaynie; Assefa Andargie (PLoS ONE, 2021)
Background Even though maternal health was highly targeted in different global strategies, maternal mortality could not be decreased as was expected. Besides this, prior decomposition analysis to the possible cause of changes to timely first antenatal booking has not been conducted. Therefore, this study aimed to assess determinants of change in timely first antenatal booking among pregnant women in Ethiopia. Methods The study utilized three consecutive Ethiopia Demographic and Health Survey (EDHS) datasets which were collected through cross-sectional study design. The number of pregnant women who gave birth in 2005, 2011 and 2016 survey included in the analysis was 7,307, 7,908 and 7,590 respectively. The data were analyzed by using Stata/SE version 14.0. Logit-based decomposition analysis was done to identify contributing factors for change in timely first antenatal booking and statistical significance was determined by using P-value. Results The trend of timely first antenatal booking was increased from 6% to 20% in the last ten years. The analysis revealed that 14% of the overall change was because of the change in women's composition. Changes in the composition of women according to region, education and occupation status were the major sources of this change. The remaining, 86% of the change was due to differences in the coefficient. Mostly, the change in behaviors of the Oromia population, those who have lived in the rural areas and male household head were some of the contributing factors for the increase in timely first antenatal booking. Conclusions There was a significant increase in timely first antenatal booking among pregnant women in Ethiopia from 2005 to 2016 EDHS. The change in the women composition according to residency, education and occupation status of women and the difference in behaviors like: behavior of rural residents and male household head contributed to the majority of the change. Interventions targeting the male household head, rural residents and those women who lived in the Oromia region should be emphasized to increase further timely booking. In addition, promoting women in terms of education and creating job opportunities could be the other recalled intervention areas of the country.